Characteristics Predicting a High Caregiver Burden in Patients with Vascular Cognitive Impairment: Using the Apriori Algorithm to Delineate the Caring Scenario [Corrigendum] - Jhang, Kai-Ming; Wang, Wen-Fu; Chang, Hsin-Fang; Chang, Ming-Che; Wu, Hsin-Hung (Risk management and healthcare policy, 2021)
Jhang KM, Wang WF, Chang HF, Chang MC, Wu HH. Risk Manag Healthc Policy. 2021;14:1335-1351. Page 1336, Patients and Methods section, second sentence, the text "(CCH IRB 160165)" should read "(CCH IRB 160615)". The authors apologize for this error. Read the original article